Efektivitas Pelayanan Perizinan Berbasis Digital di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Ciamis - Robi Robi; Irfan Nursetiawan; Neti Sunarti (GLOBAL SCIENTS PUBLISHER, 2025)
Advances in information technology have encouraged the government to adopt digital based public services to improve efficiency, transparency, and accessibility. The Investment and Integrated Services Agency (DPMPTSP) of Ciamis Regency is one of the institutions that has implemented the Online Single Submission (OSS) system as an innovation in business licensing services. This study aims to determine the effectiveness of licensing services using the OSS digital system as its main tool. The method used is qualitative with a descriptive approach. The results of the analysis show that digital-based licensing services at the Investment and Integrated Services Agency (DPMPTSP) of Ciamis Regency are not yet running effectively. This is because its implementation is still hampered by low public understanding, limited supporting facilities and infrastructure, and suboptimal cross-sector coordination.